2013
DOI: 10.3389/fpls.2013.00489
|View full text |Cite
|
Sign up to set email alerts
|

Comparative profiling of miRNA expression in developing seeds of high linoleic and high oleic safflower (Carthamus tinctorius L.) plants

Abstract: Vegetable oils high in oleic acid are considered to be advantageous because of their better nutritional value and potential industrial applications. The oleic acid content in the classic safflower oil is normally 10–15% while a natural mutant (ol) accumulates elevated oleic acid up to 70% in seed oil. As a part of our investigation into the molecular features of the high oleic (HO) trait in safflower we have profiled the microRNA (miRNA) populations in developing safflower seeds expressing the ol allele in com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 66 publications
3
26
0
Order By: Relevance
“…Furthermore, Cao et al (2013) investigated the molecular basis of the high oleic (HO) trait in safflower and compared the miRNA populations in developing safflower seeds expressing the olallele in comparison to the wild-type high linoleic (HL). They detected 55 known miRNAs and identified two novel miRNA families of developing safflower seeds.…”
Section: Functional Genomics For Drought Tolerancementioning
confidence: 99%
“…Furthermore, Cao et al (2013) investigated the molecular basis of the high oleic (HO) trait in safflower and compared the miRNA populations in developing safflower seeds expressing the olallele in comparison to the wild-type high linoleic (HL). They detected 55 known miRNAs and identified two novel miRNA families of developing safflower seeds.…”
Section: Functional Genomics For Drought Tolerancementioning
confidence: 99%
“…A list of 13 miRNAs differentially expressed between mid-maturity seeds from two genotypes of the ancient oilseed crop safflower (Carthamus tinctorius L.), with contrasting fatty acid profiles, delivered some potential candidates to pursuit functional studies. Three of these miRNA candidates, highly expressed by the genotype producing seed oil with considerably higher oleic acid content, namely miR395, miR397 and miR5026 (Cao et al 2013) seemed particularly relevant. In canola (Brassica napus), sRNAs involvement in lipid metabolism has been covered from early embryogenesis to maturation Wang et al 2016), revealing differences between high-and low-oilcontent siliques right at early embryogenesis.…”
Section: Transition To Maturation and Accumulation Of Storage Productsmentioning
confidence: 99%
“…Recent sRNA research related to oilseed content provides further examples of how specific miRNA-target interactions can be potentially used in breeding to improve seed nutritional value (Cao et al 2013;Zhao et al 2012;Wang et al 2016) or biodiesel production (Cao et al 2013;Galli et al 2014). Contrasting oilseed content genotypes appear to share a small percentage of unique sRNA sequences (Cao et al 2013), and available studies suggest some miRNAs are possibly associated with the different metabolic profiles presented by high-and low-oil-content seeds.…”
Section: Transition To Maturation and Accumulation Of Storage Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…48 miR5021 was also reported in a few plant species such as peach, ginseng, sunflower, radish, longan, Jatropha curcas, moth orchid, Brassica oleracea, and Arabidopsis. 24,26,[49][50][51][52][53][54] It was indicated that miR5021 families may be involved in the regulation of lipid metabolism and responses to stress, and MYB proteins and SPL3 transcription factor may be the target of miR5021. 26 Although miR156-3p, miR1522, miR5658, miR5783, and miR5998 were also identified in other species, their functional roles remain unknown as yet.…”
Section: Characterization Of Potential Mirnas In Blueberrymentioning
confidence: 99%